Protecting unauthorized immigrant mothers improves their children's mental health - Hainmueller, Jens; Lawrence, Duncan; Martén, Linna; Black, Bernard; Figueroa, Lucila; Hotard, Michael; Jiménez, Tomás R; Mendoza, Fernando; Rodriguez, Maria I; Swartz, Jonas J; Laitin, David D (Science (American Association for the Advancement of Science), 2017)
The United States is embroiled in a debate about whether to protect or deport its estimated 11 million unauthorized immigrants, but the fact that these immigrants are also parents to more than 4 million U.S.-born children is often overlooked. We provide causal evidence of the impact of parents' unauthorized immigration status on the health of their U.S. citizen children. The Deferred Action for Childhood Arrivals (DACA) program granted temporary protection from deportation to more than 780,000 unauthorized immigrants. We used Medicaid claims data from Oregon and exploited the quasi-random assignment of DACA eligibility among mothers with birthdates close to the DACA age qualification cutoff. Mothers' DACA eligibility significantly decreased adjustment and anxiety disorder diagnoses among their children. Parents' unauthorized status is thus a substantial barrier to normal child development and perpetuates health inequalities through the intergenerational transmission of disadvantage.